PLIN2 IS AN ARYL HYDROCARBON RECEPTOR TRANSCRIPTIONAL TARGET AND MAY CONTRIBUTE TO MUCOSAL RESTITUTION. (22nd January 2022) - Davis, Deanna; Ciorba, Matthew; Alvarado, David
Abstract: INTRODUCTION: Dysregulated barrier function contributes to the pathogenesis in inflammatory bowel diseases (Crohn's (CD) and ulcerative colitis (UC)). The cytosolic transcription factor aryl hydrocarbon receptor (AHR) is activated by both endogenous and exogenous ligands, and functionally contributes to maintaining mucosal homeostasis. Recently, we demonstrated that AHR activity promotes a pro-restitutive program in small intestine, but this pathway is disrupted in Crohn's disease. In this study, we sought to identify genetic loci associated with AHR pathway dysfunction and to identify candidate downstream effectors linking AHR activity to mucosal healing. METHODS: Organoid lines were established with biopsies from healthy patients (N=4) and patients with IBD (CD=4, UC=5) and from mice with intact Ahr (WT) or Ahr null (KO). Genomic DNA was isolated and genotyped with a custom GSA SNP chip. Organoids were differentiated and treated with AHR agonist 6-Formylindolo[3, 2-b]carbazole (FICZ) or vehicle. Expression of AHR transcriptional target cytochrome P450 1A1 (CYP1A1) was determined by quantitative realtime (qRT) PCR and was used to measure AHR activity. Genomic association analysis was performed using PLINK with cell lines with high (>3 fold) CYP1A1 expression as controls and cells with low CYP1A1 expression as cases. RESULTS: Using human organoids, nine genetic variants were associated with low AHR activity (p<5x10 -8 ). One variant, rs12338361, has been identified as an expression quantitative trait locus (eQTL) for Perilipin 2 (PLIN2) in other tissues. PLIN2 is involved in lipid droplet formation and trafficking in the liver, but has also been shown to be a PPARγ effector and reduce inflammation by lowering the release of TNFa in the intestine. In WT mouse organoids, expression of Plin2 was increased in response to FICZ treatment (∼50% increase). This upregulation was dependent on Ahr, as Plin2 expression did not increase in KO mouse organoids (∼7% increase). Expression of PLIN2 was assessed in human organoids treated with FICZ and was found to correlate with AHR activity (r=0.953, p=4.896 x 10 -7 ). CONCLUSIONS: PLIN2 is a transcriptional target of AHR and may contribute to AHR-mediated epithelial restitution through activation of the PPARγ pathway. This may represent a novel method of controlling inflammation in the intestinal epithelium.